Review of Active Front-End Rectifiers in EV DC Charging Applications - Assel Zhaksylyk; Haaris Rasool; Ekaterina Abramushkina; Sajib Chakraborty; Thomas Geury; Mohamed El Baghdadi; Omar Hegazy (Batteries, 2023)
Active Front-End (AFE) rectifiers have regained momentum as the demand for highpower Electric Vehicle (EV) charging infrastructure increases exponentially. AFE rectifiers have high efficiency and reliability, and they minimize the disturbances that could be generated due to the operation of the EV charging systems by reducing harmonic distortion and operating close to the Unity Power Factor (UPF). The purpose of this review is to present the current state-of-the-art AFE rectifiers used in fast chargers, focusing on the comparison between different AFE topologies and their components, as well as modular AFE solutions. Furthermore, different control strategies of AFE converters are presented and compared. Some of their more widely used control techniques, namely Voltage Oriented Control (VOC), Direct Power Control (DPC), Hysteresis Current Control (HCC), and Model Predictive Control (MPC), have been implemented, and their performance compared. Centralized and distributed control systems are compared for operating parallel AFE rectifiers for modular, fast charging systems. An overview of cooling systems and reliability evaluation tools is also presented. Finally, trends and future outlooks are analyzed.